Visual Ethnography and Childhood: Photography and Visual Archive in Educational Research - Álvarez-Barrio, Carla; Mesías-Lema, José María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Ethnography, photography, and education have a lot in common when we talk about childhood. This article aims to reflect on possible dialogues and connections between these three elements. The methodology to achieve this combines a powerful bibliographic review, visual documentation, and analysis of real and updated experiences that involve children as an active participant in the research. The conclusions obtained defend artistic language and visual narratives as an effective part of ethnographic research. In this way, we will focus on the role of childhood within the photographic visual archive and its transition from object to subject of study capable and eager to tell its own story in the first person.